1997
DOI: 10.1109/10.563302
|View full text |Cite
|
Sign up to set email alerts
|

Respiration response curve analysis of heart rate variability

Abstract: A noninvasive study was conducted on intact awake humans to characterize the dynamic response of the heart to the vagus during slow-, comfortable-, and fast-paced respiration (8, 12, and 18 breaths/min), under both sitting and standing conditions. The respiration response curve (RRC) of respiration-associated vagal effects on the heart was estimated, and characteristics of entrainment and frequency dependence on respiration were demonstrated. It was shown that the degree of entrainment and magnitude of phase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Another interesting signal to be considered in a hyperbaric study is the respiratory one, which can be extracted from ECG or PPG [13] - [19]. In this regard, it has been shown that changes in the respiratory pattern alter the spectral content of HRV [20] and, consequently, the interpretation of sympathetic or vagal activations [21] - [23].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting signal to be considered in a hyperbaric study is the respiratory one, which can be extracted from ECG or PPG [13] - [19]. In this regard, it has been shown that changes in the respiratory pattern alter the spectral content of HRV [20] and, consequently, the interpretation of sympathetic or vagal activations [21] - [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods cannot describe a precise phase relation between respiration and multiple cardiovascular variables, because respiration is not a linear or harmonic oscillator. One solution to this problem is to use paced respiration (12,24,31), but this investigates the respiratory influence only in a specific condition, and the pacing itself may result in unnatural hyperventilation or an alteration in the autonomic balance (19). Therefore, an analysis that represents respiration as a nonlinear oscillator, thus focusing on the respiratory phase, is required.…”
mentioning
confidence: 99%
“…The result is the dynamic pattern of R-R interval change along the respiratory cycle. Several researchers have applied the method to investigating magnitude (5,23,25,27) and phase properties (5,14,17,25,26) of RSA.…”
mentioning
confidence: 99%